Effect of maltodextrin level on nutritional and physicochemical properties of spray-dried mandarin juice - AHMAD, ILHAM; MURSALIM, MURSALIM; SALENGKE, SALENGKE; WARIS, ABDUL; JASSIN, ERNAWATI; ARISANDI, ARWINI (Asian Journal of Agriculture, 2026)
Abstract. Ahmad I, Mursalim, Salengke, Waris A, Jassin E, Arisandi A. 2026. Effect of maltodextrin level on nutritional and physicochemical properties of spray-dried mandarin juice. Asian J Agric 10 (1): g100118. https://doi.org/10.13057/asianjagric/g100118. Spray drying is widely used to transform heat-sensitive fruit juices into shelf-stable powders. However, the addition of carrier agents can diminish the retention of labile nutrients. The influence of maltodextrin-to-mandarin juice ratios ranging from 15:85 to 45:55 (w/w) on spray-dried powder properties was evaluated at a fixed inlet temperature of 130°C. Seven formulations of Selayar mandarin (Citrus reticulata) juice with food-grade maltodextrin (DE 10-12) were homogenized and spray-dried using a Büchi B-290 mini spray dryer (outlet 85-115 °C) with a two-fluid nozzle (6 bar), feed rate of ~5 mL/min, and 100% aspirator. Each formulation was processed in triplicate. Vitamin C content was determined by DCPIP titration, titratable acidity (TAT) was measured as percent citric acid, moisture content was determined by oven-drying at 105 °C, ash content by muffle furnace at 550°C, and soluble solids (°Brix) by digital refractometry. Results are reported as mean ± SD (n=3), and the effect of carrier level was analyzed by one-way ANOVA followed by Tukey’s HSD test (p < 0.05). Vitamin C content of the powder was significantly reduced from 259.98 mg/100 g to 135.14 mg/100 g as the maltodextrin content increased, and titratable acidity was lowered from 1.28% to 0.35%. Moisture content remained low (3.54-4.47%), indicating that the powders were sufficiently dried for safe storage. Ash content increased from 0.13% to 0.48% at higher maltodextrin ratios, whereas °Brix values remained high (75.0-85.1), indicating strong retention of soluble solids. Overall, a clear trade-off was observed between nutrient preservation and powder stability: greater vitamin C retention was achieved at lower carrier-to-juice ratios, whereas higher ratios were associated with improved drying performance and powder handling. These findings provide practical guidance for optimizing carrier use in small-scale citrus powder production and underscore the need for further research on alternative carrier materials and their effects on sensory quality.
Keywords: Citrus powder, physicochemical properties, spray drying, vitamin C degradation